1999
DOI: 10.1210/jcem.84.5.5681
|View full text |Cite
|
Sign up to set email alerts
|

“Hot Spot” in the PROP1 Gene Responsible for Combined Pituitary Hormone Deficiency1

Abstract: As pituitary function depends on the integrity of the hypothalamic-pituitary axis, any defect in the development and organogenesis of this gland may account for a form of combined pituitary hormone deficiency (CPHD). Although pit-1 was 1 of the first factors identified as a cause of CPHD in mice, many other homeodomain and transcription factors have been characterized as being involved in different developmental stages of pituitary gland development, such as prophet of pit-1 (prop-1), P-Lim, ETS-1, and Brn 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 26 publications
0
14
0
6
Order By: Relevance
“…The highest frequencies of patients affected by PROP1 mutations were reported for East-Central and Eastern Europe [31], pointing to a founder effect. Most of the mutations identified so far are represented by just two gene variants: c.296delGA (previously referred to as c.301_302delGA) and c.150delA [32]. These typical mutations were also found in all three patients with PROP1 changes in our cohort.…”
Section: Discussionmentioning
confidence: 55%
“…The highest frequencies of patients affected by PROP1 mutations were reported for East-Central and Eastern Europe [31], pointing to a founder effect. Most of the mutations identified so far are represented by just two gene variants: c.296delGA (previously referred to as c.301_302delGA) and c.150delA [32]. These typical mutations were also found in all three patients with PROP1 changes in our cohort.…”
Section: Discussionmentioning
confidence: 55%
“…1). The three tandem repeats of the GA dinucle- otides at location 296-302 represent the "hot-spot" region for mutation, and mutations involving this region cause preterm truncation of the homeodomain (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Most reports indicate that in the Caucasian population PROP1 gene mutations are frequently found in patients with non-acquired, familial forms of CPHD (19,20,23). In a study reported from the Czech Republic, 18 of 74 patients with CPHD had homozygous or heterozygous mutations of the PROP1 gene (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PROP-1 is necessary for the activation of the POU1F-1 gene, the human homolog of mouse Pit-1 (13,14). Defects in the PROP-1 gene may cause deficiencies in pituitary hormones produced by POU1F-1-dependent cell lineages (somatotrophs, thyrotrophs, lactotrophs), as well as gonadotrophin and corticotrophin deficiencies (3)(4)(5)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%